The Sight-Lovers of Republic V and Plato’s Critique of their Ontology - Panayides, Christos Y. (Peitho. Examina Antiqua, 2025)
In Republic V 474b3–480a13, Plato initiates a discussion that is intended to define who the philosophers are that must rule the city. In the context of this discussion, we are told that the sight-lovers are among the pretenders to the title of the philosopher. This paper addresses the following questions about the sight-lovers: “Who are the sight-lovers of Republic V?”; “Do they maintain some kind of coherent ontological position?”; and, “If they do, then what is its content, and how does Plato attempt to rebut it?”. In particular, it is argued that: (1) The sight-lovers of Republic V maintain that the objects of our everyday experience are bundles of things such as colors and shapes; (2) Plato presents his own position about the nature of concrete particulars in the Phaedo (Phd. 102a11–103a3); (3) This discussion in the Phaedo may facilitate our effort to place the sight-lovers thesis in its proper setting and also parse its finer details; and (4) Plato spells out his critique of the sight-lovers’ position in Republic VII (R. 523a5–524d4) in the context of his treatment of the summoners.